Determination ambroxole hydrochloride in substance ambroxole hydrochloride and finish medical products by methods adsorption spectroscopy in ultraviolet area, thin layer chromatography and height performers liquid chromatography - І. V. Nigencovska; O. V. Burmaka; О. V. Manchenko; К. E. Ziskind (The State Expert Center of the Ministry of Health of Ukraine, 2020)
The determination of the qualitative and quantitative content of the main active substance of a microlitic medicinal product is necessary to confirm its good quality. The purpose of scientific research: check the suitability of existing methods for the qualitative and quantitative determination of ambroxol hydrochloride, as indicated in the monographs of the SPU «Ambroxol hydrochloride, substance» and «Ambroxol tablets», for the possibility of qualitative and quantitative determination of ambroxol hydrochloride in various finished medicines and to determine the possibility of using an alternative solvent in individual methods. The substance of Ambroxol hydrochloride and four finished dosage forms with the active substance Ambroxol hydrochloride were used: injection solution 7.5 mg/ml in ampoules, 30 mg tablets, syrup 15 mg/5 ml and a combined drug that contains 30 mg Ambroxol hydrochloride and acetylcysteine 200 mg in powder form for oral suspension in sachet. The study was carried out using a UV spectrophotometer, an Agilent 1200 liquid chromatograph with a diode array detector (chromatographic column ‒ Inertsil ODS-3V, 250×4.6 mm, particle size 5 μm), thin-layer chromatography (chromatographic plate ‒ TLC Silicagel 60 F254). The suitability of using an alternative solvent with a 0.1 M hydrochloric acid solution to identify the substance of ambroxol hydrochloride by UV spectrophotometry, as indicated in the SPU monograph for Ambroxol hydrochloride, substance, has been confirmed. As a result of the study of finished dosage forms, it was determined that the identification of ambroxol hydrochloride with a 0.1 M hydrochloric acid solution is possible only for injection and tablets. For syrup and powder for oral suspension, it was determined that the use of such a technique for the identification of ambroxol hydrochloride is impossible. According to the results of the quantitative determination of ambroxol hydrochloride according to the methodology of the SFU «Ambroxol tablets» monograph in different dosage forms, it is possible to conclude that this technique is suitable for such forms as injection and syrup. For the quantitative determination of ambroxol hydrochloride in a preparation in the form of a powder for oral solution, this technique is unsuitable. Using thin layer chromatography, it is possible to identify Ambroxol hydrochloride for such forms as tablets and injection. However, the unsuitability of this methodology for such forms of as powder for oral suspension and syrup. It was confirmed that the experimentally selected technique using the method of high performance liquid chromatography is suitable for the qualitative and quantitative determination of ambroxol hydrochloride in the finished drugs that are selected for this work, and can be used to test finished drugs with the same composition of active and excipients. It was found that the method of high performance liquid chromatography allows not only to identify and quantify ambroxol hydrochloride, but also to determine the presence of some excipients.